РОЛЬ И ЗНАЧЕНИЕ ФИЗИЧЕСКОЙ КУЛЬТУРЫ И СПОРТА ДЛЯ ЭКОНОМИКИ И ОБЩЕСТВА - Гапурбаева, Ш. Р. (Journal of Economic Research & Business Administration, 2015)
In the following article I investigate the problem of developing sport market services in modern Kyrgyzstan.